Typology and Components of Telajakan Subak: A Sustainable Landscape Model in Anggabaya Village, Bali, Indonesia - I Made Agus Dharmadiatmika; Naniek Kohdrata; Kadek Edi Saputra; Ni Made Diah Ayu Kendran; Lury Sevita Yusiana; Adrian Schellhorn (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
This study explores the Subak agricultural landscape in Anggabaya Village, Denpasar, Bali, focusing on its role in sustaining socio-cultural, religious, and ecological practies. Central to this research in the Telajakan Subak, examined to identify and classify its typologies and structural components through an architectural framework. Using qualitative methods, the study involves field surveys, spatial documentation, and interviews. The analysis is guided by five architectural principles and function. Findings reveal diverse Subak typologies influenced by irrigation infrastructure, accessibility, and topography, including both organic and constructed models. These results demonstrate that Telajakan Subak serves as a vital model for sustainable landscape management. This research contributes to vernacular landscape architecture and supports integrating traditional systems into modern urban-rural planning, ensuring the resilience of Balinese cultural landscapes amid suburban pressures.